A Return to the Walking City: Consumer Experience and the History of Transportation and Business on State Street in Madison, Wisconsin - Wein, Cameron; Nehls, Breana; Mullendore, Katya; Fadelli, Katherine (My University, 2016)
Directly connecting the Wisconsin State Capitol and the eastern edge of the University of Wisconsin - Madison, State Street has long been the premier transportation artery as well as the cultural and economic heart of the city. In order to track how the shifts in transportation affected the business landscape at this micro-scale, the authors collected and categorized the businesses present on State Street throughout selected years of 1858 to 2014. Trends of the four business categories that the authors identified changed in relation to the major transportation events on State Street, such as the implementation and removal of the streetcar and the conversion to a transit mall. State Street’s identity evolved from a thoroughfare that supported industry and staple goods to a pedestrian focused shopping and entertainment destination. Our review of archival business directories shows that transportation and the business landscape co-evolved through time.
Includes images, maps, figures, tables, bibliography
Keywords: Business; Pedestrian; Transportation; Wisconsin; Madison; State Street